Income Inequality and Economic Growth - Sutanto, Himawan; Harsono, Iwan; Furkan, Lalu M.; Mulawiani, Baiq Saripta Wiji; Fuady, Helmy; Yuniarti, Titi (Economics Studies and Banking Journal (DEMAND), 2024)
This research investigates the relationship between income inequality, income distribution, poverty rates, and economic growth. The analysis results indicate that the independent variables, including the Gini Coefficient, Percentage of Income Received by Specific Groups, and Relative Poverty Rate, significantly influence economic growth. High levels of income inequality, uneven income distribution among societal groups, and high poverty rates all contribute to the slowdown of economic growth. Therefore, policies aimed at reducing income inequality, improving equitable income distribution, and decreasing relative poverty rates can help stimulate more inclusive and sustainable economic growth.